Mitochondrial dysfunction is a key link involved in the pathogenesis of sick sinus syndrome: a review - Shi, Xinxin; He, Liming; Wang, Yucheng; Wu, Yue; Lin, Dongming; Chen, Chao; Yang, Ming; Huang, Shuwei (Frontiers in Cardiovascular Medicine, 2024)
Sick sinus syndrome (SSS) is a grave medical condition that can precipitate sudden death. The pathogenesis of SSS remains incompletely understood. Existing research postulates that the fundamental mechanism involves increased fibrosis of the sinoatrial node and its surrounding tissues, as well as disturbances in the coupled-clock system, comprising the membrane clock and the Ca2+ clock. Mitochondrial dysfunction exacerbates regional tissue fibrosis and disrupts the functioning of both the membrane and calcium clocks. This plays a crucial role in the underlying pathophysiology of SSS, including mitochondrial energy metabolism disorders, mitochondrial oxidative stress damage, calcium overload, and mitochondrial quality control disorders. Elucidating the mitochondrial mechanisms involved in the pathophysiology of SSS and further investigating the disease's mechanisms is of great significance.